The Effects of Valence and Arousal on Associative Working Memory and Long-Term Memory - Bergmann, Heiko C. (Public Library of Science, 2012)
BACKGROUND: Emotion can either facilitate or impair memory, depending on what, when and how memory is tested and whether the paradigm at hand is administered as a working memory (WM) or a long-term memory (LTM) task. Whereas emotionally arousing single stimuli are more likely to be remembered, memory for the relationship between two or more component parts (i.e., relational memory) appears to be worse in the presence of emotional stimuli, at least in some relational memory tasks. The current study investigated the effects of both valence (neutral vs. positive vs. negative) and arousal (low vs. high) in an inter-item WM binding and LTM task. METHODOLOGY/PRINCIPAL FINDINGS: A five-pair delayed-match-to-sample (WM) task was administered. In each trial, study pairs consisted of one neutral picture and a second picture of which the emotional qualities (valence and arousal levels) were manipulated. These pairs had to be remembered across a delay interval of 10 seconds. This was followed by a probe phase in which five pairs were tested. After completion of this task, an unexpected single item LTM task as well as an LTM task for the pairs was assessed. As expected, emotional arousal impaired WM processing. This was reflected in lower accuracy for pairs consisting of high-arousal pictures compared to pairs with low-arousal pictures. A similar effect was found for the associative LTM task. However, the arousal effect was modulated by affective valence for the WM but not the LTM task; pairs with low-arousal negative pictures were not processed as well in the WM task. No significant differences were found for the single-item LTM task. CONCLUSIONS/SIGNIFICANCE: The present study provides additional evidence that processes during initial perception/encoding and post-encoding processes, the time interval between study and test and the interaction between valence and arousal might modulate the effects of “emotion” on associative memory.